The Role of Principles of Positive Accounting Theory in Organizations Success in the Private University in Erbil- Kurdistan Region - Rebin Bilal Mohammed; Ronyaz Hayyas Mahmood; Mohammed Ghazi Rafaat (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
This paper aims to investigate the influence of PAT principles on organizational success within private universities in Erbil, Kurdistan Region. To achieve these objectives, a survey was undertaken among a sample of 65 Leader members at a private University located in Erbil. The survey data was extensively analyzed by the researchers using the Statistical Package for the Social Sciences (SPSS). The study utilizes correlation and regression analyses to reveal a significant positive link between principles of Positive Accounting theory (PAT) and the perception of organizational success among university Leader members. The results collectively underscore the importance of conservative accounting practices, accurate recognition and measurement of economic events, transparent disclosure practices, and the provision of useful financial information in contributing to organizational success. Among the study reccomedations, private universities are urged to consider adopting conservative accounting practices for enhanced financial stability and success, emphasizing prudence in recognizing losses and avoiding overoptimistic reporting.